Opportunity and Threats of Surabaya Sightseeing City Tour Bus Program in The Promotion of Tourism Destinations to Foreign Tourists - Putri, Nadiya Ivany (Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pasundan, 2025)
The purpose of this study is to assess how well the Surabaya Sightseeing City Tour Bus (SSCT) program works to make Surabaya a more alluring tourist destination for international visitors. This research looks at how SSCT works as a tool for branding Surabaya city to foreign tourists. This research uses descriptive qualitative method which is one of the effective approaches to describe a practice. Direct observation during the internship, interviews with staff at the tourist information center, and analysis of 2024 visitor visit data were used to collect data. The findings show that although the Surabaya Sightseeing City Tour (SSCT) program successfully integrates local culture in the city branding strategy through strong historical narratives and cultural experiences, limitations in global promotion, digital access, and multilingual support are the main challenges in effectively reaching foreign tourists. With this, the author identifies opportunities in the SSCT program by expanding promotional channels, improving accessibility for international payments, and strengthening internationally packaged local cultural narratives are some of the recommendations.